Switzerland : 2021 Article IV consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Switzerland. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Switzerland has navigated the COVID-19 pandemic well. The pandemic has had major social and economic impacts, but an early, strong, and sustained health and economic policy response helped contain the contraction of activity. Coordinated efforts targeting households and firms stemmed a loss of purchasing power and a rise of unemployment and bankruptcies. Recovery has commenced, but uncertainty and risks remain high, dominated by pandemic dynamics. The rebound should deepen, as vaccination proceeds, containment is eased, and domestic and global demand picks up. Fiscal support has been rightly extended in 2021, and monetary policy remains accommodative. Policies should remain supportive until there are clear signs of sustained recovery; the authorities should expand support if needed. Redirection to fostering green, digital transformation with attention to low-income earners will be needed, including to ensure that prolonged emergency support does not hinder structural changes in the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Switzerland